2021
DOI: 10.3390/su13020497
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance and Physical Activities as Positive Factors for Life Satisfaction among University Students

Abstract: Life satisfaction influences sustainable personal growth among students by ensuring that they more firmly apply themselves in their education. Universities represent an environment where students may improve their life satisfaction through better academic performance and being engaged in extracurricular sport. This study evaluates life satisfaction (LS) among university students, 18 to 28 years of age to confirm whether academic performance, involvement in sports and physical activity are factors relating to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…In addition, the majority also indicated that their scope of free time increased during the pandemic. This trend can be another illustration of the previous studies indicating young people's inability to self-engage into improving their physical and mental health (12,13), despite the fact of having more free time during the pandemic that is mostly spent alone.…”
Section: Resultssupporting
confidence: 60%
“…In addition, the majority also indicated that their scope of free time increased during the pandemic. This trend can be another illustration of the previous studies indicating young people's inability to self-engage into improving their physical and mental health (12,13), despite the fact of having more free time during the pandemic that is mostly spent alone.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, while mental well-being, selfreported health, and age can explain 40.7% of the variances of the satisfaction with life, there may be other factors contributing to college students' life satisfaction. Other factors found in the literature that are linked with life satisfaction are satisfaction with family life (Schnettler et al, 2017), stress and ego-resilience (Kim & Koh, 2016), and academic performance, and physical activities (Slavinski et al, 2021), among others. Future researchers may consider these variables when studying life satisfaction in the current or similar context.…”
Section: Discussionmentioning
confidence: 99%
“…When the body does sports activities, the body will produce beta-endorphins which have the effect of improving mood. Optimal physical activity affects quality of life [24].…”
Section: Correlation Between Physical Activity and Stressmentioning
confidence: 99%